English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^2 -8x +12

2007-07-26 11:16:03 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

Since x^2 has a coefficient of 1, this is a simpler factoring problem; look at the factors of 12 & see which pair add up to -8

1,12 ; sum is 13, nope
-1,-12; no
2,6; no
-2,-6; sum is -8, and this is what you are looking for

x^2 -8x + 12 = (x-2)(x-6)

2007-07-26 11:23:19 · answer #1 · answered by Optimizer 3 · 0 0

x^2-8x+12=(x-2)(x-6)

2007-07-26 18:21:21 · answer #2 · answered by Anonymous · 0 0

x^2 - 8x + 12 = 0
x = [8 +- Sq Rt (64 - 48)]/2
x = (8 +- 4)/2
x = 6
x = 2
(x-6)(x-2) = x^2 -8x + 12

2007-07-26 18:44:24 · answer #3 · answered by robertonereo 4 · 0 0

(x-6)(x-2)

2007-07-26 18:31:25 · answer #4 · answered by Anonymous · 0 0

(x-2)(x-6)

2007-07-26 18:19:40 · answer #5 · answered by Ronatnyu 7 · 0 0

fedest.com, questions and answers